Investigating the possible cytoprotective effects of melatonin isomer against simulated ischemic injury - Victor, Laikyn (Department of Medicine, 2018)
Introduction: The presence of melatonin in wine contributes to the cardioprotective effect of regular and moderate consumption of wine against lethal ischemia/reperfusion injury. Recently, the presence of melatonin isomers has been identified in red wine, but whether or not these isomers confer any physiological properties is unknown. Aim: The aim of our study was to establish a cell culture model of simulated ischemia to study and compare the possible cytoprotective effects of dietary melatonin and a melatonin isomer against an ischemic insult and to explore the possible role of melatonin receptors in this effect. Methods: H9C2 cardiac fibroblast cells were subjected to simulated ischemia by exposure to 1mM H₂O₂ following a 30min pre-treatment with 75ng/L (dietary concentration), 1μM (pharmacological concentration, 0.232mg/L) melatonin or/and 75mg/L (dietary concentration) melatonin isomer. To determine the role of melatonin receptors, cells were pre-treated with the melatonin receptor inhibitor, luzindole (10 μM) for 1h prior to H₂O₂ treatment. At the end of the simulated ischemic insult, cell viability was assessed using trypan blue staining. Mitochondrial respiration in permeabilized H9C2 cells was measured using the Oroboros Instrument, at two different time points: at the end of a 30min pre-treatment with either 75ng/L melatonin or 75mg/L melatonin isomer, or the afore mentioned pre-treatments prior to a 15min treatment of 1mM H₂O₂. Results: A simulated ischemic insult with 1mM H₂O₂ reduced cell viability from 92.9±1.5% to 28.4±1.4% (p<0.001 vs control). Pre-treatment with the dietary concentrations of melatonin or the melatonin isomer improved the cell viability to a similar extent as a pre-treatment with the pharmacological concentration of melatonin (74.4±3.1%, 73.9±2.7% and 69.0±1.2%, p<0.001 vs H₂O₂ and p<0.01 vs H₂O₂ respectively). A combined pre-treatment of melatonin and the melatonin isomer did not add further cytoprotective benefit. Addition of luzindole fully abolished the cytoprotective effect of dietary melatonin (29.7±2.4%, p<0.001 vs H₂O₂ + Mel), but only partially abolished the cytoprotective effect of the melatonin isomer (41.4±3.6%). Both dietary concentrations of melatonin and the melatonin isomer did not affect mitochondrial respiration in permeabilized H9C2 cells. Conclusion: Our findings suggest that both dietary melatonin and the melatonin isomer confer cytoprotection against a simulated ischemic insult, an effect which is mediated, at least in part, via the activation of melatonin receptors. Both melatonin and melatonin isomers present the advantage to be potentially safe and inexpensive therapies against ischemic heart disease.